Empowerment of the Environment Through the Utilization of Organic Waste as Raw Material for Organic Fertilizer Production in Pandan Wangi Village - Makki, Muhammad; Hawarikatun, Baiq; Safitri, Dwi; Rizky Anjani, Alifiya; Azwari, Mila; Pratama, Sanjaya; Azzahra, Fatima; Farid Irfansyah, Muhammad; Adellya, Putri; Reihan Pratama, Rio; Mukarom, Amar (Unram Journal of Community Service, 2025)
The use of fertilizers plays an important role in increasing agricultural productivity. However, long-term dependence on chemical fertilizers poses a risk of reducing soil fertility, causing nutrient imbalances, and leading to the accumulation of chemical residues that negatively impact the soil ecosystem. Pandan Wangi Village, which develops the agricultural and livestock sectors side by side, still faces challenges in managing organic waste. This condition leads to environmental pollution and a high dependence on chemical inputs in agriculture. This program aims to reduce the use of chemical fertilizers by utilizing livestock waste as a raw material for organic fertilizers, which can enhance soil fertility and reduce environmental impacts. This activity involves socialization and training to improve the knowledge and skills of the community in independently producing organic fertilizers. This program is expected to provide long-term benefits for agricultural productivity and empower communities towards a more sustainable and environmentally friendly agricultural system.